Differential activation of nuclear factor kappa B subunits in a skin dendritic cell line in response to the strong sensitizer 2,4-dinitrofluorobenzene - Cruz, MT (2010)
Dendritic cell (DC) maturation is essential for the initiation of T-dependent immune responses. Nuclear factor kappa B (NF-kappaB) transcription factors are ubiquitously expressed signalling molecules, known to regulate the transcription of a large number of genes involved in immune responses, including cytokines and cell surface molecules. In this work, we studied the time-dependent activation of five members of the NF-kappaB family, p50, p52, p65, RelB and cRel, in a mouse skin DC line in response to stimulation with the strong sensitizer, 2,4-dinitrofluorobenzene (DNFB). Western blot assay revealed that exposure of fetal skin DC (FSDC) to DNFB induced the degradation of the inhibitor of NF-kappaB (IkappaB). Three out of its five members, i.e. p50, p52, and RelB, were similarly activated upon DNFB stimulation, with subsequent translocation of these subunits from the cytosol to the nucleus, but with different kinetics. In contrast, p65 expression was diminished in both the nucleus and the cytosol. The electrophoretic mobility shift assay (EMSA) showed that exposure of FSDC to DNFB induced DNA binding to NF-kappaB. Together, these results show that DNFB differentially activates the various members of the NF-kappaB family in skin DC.